A foreign body aspiration presenting as left sided empyema and its removal by novel method - Ramniwas; Gopal Chawla; Nishant Kumar Chauhan; Naveen Dutt (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2019)
Foreign body aspiration is not very common in adults, clinically, patients either present with acute respiratory failure which require immediate intervention or with recent onset of symptoms, like wheezing, breathlessness, coughing, and expectoration. Occasionally, a forgotten or incidental foreign body may get detected on a chest radiographs which are obtained for unrelated reasons or during bronchoscopy. Identifi cation of occult foreign body aspiration often requires a high index of clinical suspicion, especially in those who present without a history of aspiration.